La formulación de las políticas públicas de turismo en México. El caso del programa federal “Pueblos Mágicos” 2001-2012 - García, Mario Alberto Velázquez (Diálogos Latinoamericanos, 2013)
This article analyzes the consequences of public policies that are developed based on socially constructed definitions of the different actors. I will focus on the national Mexican Tourism program “Magic Villages” to explore the role and impact that public policy might have on shaping the national Mexican identity. I argue that tourism is not only to be understood as an economic factor, but also as significant symbolic space of interactions in the contemporary societies.